2011
DOI: 10.1016/j.corsci.2011.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behaviour of Al/Al3Ti and Al/Al3Zr functionally graded materials produced by centrifugal solid-particle method: Influence of the intermetallics volume fraction

Abstract: Any queries or remarks that have arisen during the processing of your manuscript are listed below and highlighted by flags in the proof. Click on the 'Q' link to go to the location in the proof.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…This fact confirms that both, the untreated Al alloy substrate and laser-alloyed coatings are susceptible to pitting corrosion [60]. Further, although TiC and TiB2 coating generally exhibit good passivation behaviour in a NaCl solution, the active/Al part of the coatings prevented expressive passive plateau, as the potential continuously increases with increasing current density [1,3,60,61]. Table 1 lists the results of active dissolution potentials obtained from cyclic polarisation tests, including the average values of protective efficiency (PEF).…”
Section: Cyclic Polarizationsupporting
confidence: 55%
“…This fact confirms that both, the untreated Al alloy substrate and laser-alloyed coatings are susceptible to pitting corrosion [60]. Further, although TiC and TiB2 coating generally exhibit good passivation behaviour in a NaCl solution, the active/Al part of the coatings prevented expressive passive plateau, as the potential continuously increases with increasing current density [1,3,60,61]. Table 1 lists the results of active dissolution potentials obtained from cyclic polarisation tests, including the average values of protective efficiency (PEF).…”
Section: Cyclic Polarizationsupporting
confidence: 55%
“…She et al in 2010 experimentally confirmed the intermetallics Al 3 Zr 5 and Al 4 Zr 5 to be high temperature phases [21]. In 2011, Ferreira et al investigated the influence of Al 3 Zr volume fraction on the corrosion behavior of Al/Al 3 Zr functionally graded materials (FGM) [22]. All of these researches on the thermodynamic properties and hydrogen adsorption properties provide valuable information for the applications of Al-Zr alloys.…”
Section: Introductionmentioning
confidence: 94%
“…Among these Al-Zr intermetallics, AlZr 3 , Al 3 Zr 5 , Al 2 Zr 3 , Al 4 Zr 5 and Al 3 Zr have been investigated successively, from which Al 3 Zr is the mostly studied phase because of its supernormal role as the dispersoid precipitation and reactor core components [16,17]. In terms of the other Al-Zr intermetallics, the existing studies mainly focus on their thermodynamic properties and hydrogen adsorption properties [18][19][20][21][22]. For example, Saunders et al thermodynamically characterized the binary Al-Zr alloys in 1986, with particular emphasis on the Al-rich parts [15].…”
Section: Introductionmentioning
confidence: 99%
“…To meet the ever increasing demands, facing the trend of environment protection is one of the most important challenges in the automotive industry nowadays [1]. The researchers primarily pay attention to design concepts and the replacement of conventional materials by those of sufficient strength, lower density and good corrosion durability [2,3]. Besides, materials such as carbon fiber reinforced plastics (CFRP) are very promising candidates for new design strategies due to their specific mechanical properties [2,4,5].…”
Section: Introductionmentioning
confidence: 99%